Fatigue-induced balance impairment in young soccer players - Pau, M.; Ibba, G.; Attene, G. (Journal of Athletic Training, 2015)
Context: Although balance is generally recognized to be an important feature in ensuring good performance in soccer, its link with functional performance remains mostly unexplored, especially in young athletes.